Effect of ultrasound on the hydrophobicity of microparticles - Jordaan, Jean de Bruin (My University, 2022)
Ultrasound is used extensively in medical applications and has uses in industrial applications as well. Hydrophobic microparticles are acoustically active and are manipulated using ultrasound in various ways with applications as ultrasound contrast agents and ultrasound-guided drug delivery. The hydrophobicity of microparticles has been qualitatively observed to change when exposed to ultrasound. This phenomenon has not been previously described nor verified through a quantitative measurement technique. This research investigated and quantified the effect of ultrasound on microparticle hydrophobicity. Hydrophobic carbon black microparticles were exposed to various regimes of ultrasound. Microparticle samples were suspended in distilled water and exposed to various controlled acoustic regimes, at various frequencies of 1-10 MHz and at various amplitudes of 0-100 kPa, for 5 min. The hydrophobicity of the samples is measured using a novel technique, the colourimetric partition coefficient measurement. The partition coefficient quantifies hydrophobicity through the partitioning phenomena of octanol and water. The partitioning coefficient value is then calculated through image colourimetry and digital image processing. The microparticles exposed to the various ultrasound regimes used had their hydrophobicity reduced by 42% compared to control null samples, with a statistical significance of ≈ 3σ. This research provides the foundational knowledge for possible manipulation of microparticle hydrophobicity using ultrasound and its wide-reaching applications.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Science in Engineering to the Faculty of Engineering and the Built Environment, School of Electrical and Information Engineering University of the Witwatersrand, Johannesburg, 2022